Ferroptosis-Related Gene Signature and Patterns of Immune Infiltration Predict the Overall Survival in Patients With Lung Adenocarcinoma - Wang, Yuxuan; Chen, Weikang; Zhu, Minqi; Xian, Lei (Frontiers in Molecular Biosciences, 2021)
Abstract Background Lung adenocarcinoma (lung adenocarcinoma, LUAD is a malignant tumor with high heterogeneity and poor prognosis. Ferroptosis, an iron-dependent form of regulated cell death, has been proved can trigger inflammation-associated immunosuppression in the tumor microenvironment for promoting tumor growth. Therefore, the prognostic value of ferroptosis-related genes in LUAD needs to be further studied. Method In this study, the mRNA expression profiles and corresponding clinical data of LUAD patients were downloaded from the TCGA database. We utilized the least absolute shrinkage and selection operator (LASSO) Cox regression model to construct ferroptosis-related genes signature. Based on them, the prognosis prediction nomograms were established. The cell type identification by estimating relative subsets of RNA transcripts (CIBERSORT) algorithm was then applied to screen significant tumor immune-infiltrating cells associated with the LUAD prognosis prediction model. Then, co-expression analysis was applied to explore the relationship between ferroptosis-related genes and significant immune cells. Results Our results showed that 20 genes correlated with overall survival (OS) in the univariate COX regression analysis as prognostic differentially expressed genes (DEGs) (FDR <0.05). A 13-gene signature was constructed to stratify patients into two risk groups, which high-risk group had a significantly worse OS than their low-risk counterparts (p<0.001). We confirmed the signature's predictive capacity by receiver operating characteristic (ROC) curve analysis. Besides, we identified 7 pairs of ferroptosis-related genes and tumor-infiltrating immune cells associated with prognostic of LUAD. Conclusion we construct a novel ferroptosis-related gene signature that can be used for prognostic prediction in LUAD and reveal a possible relationship between ferroptosis and tumor-infiltrating immune cells.